2022
DOI: 10.1111/ecog.05900
|View full text |Cite
|
Sign up to set email alerts
|

Life history diversity in terrestrial animals is associated with metabolic response to seasonally fluctuating resources

Abstract: Physiological and behavioral processes interact with environmental conditions to strongly influence organismal life history strategies which covary with latitude. However, few studies have articulated explicit linkages between metabolism and life history across latitudinal gradients. Interactions between metabolism and resource dynamics may give rise not only to patterns of variation in mean life history traits, but also to patterns in the ranges (diversity) of those traits across the same gradients. Here we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 51 publications
3
14
0
Order By: Relevance
“…Interestingly, we found that phylogenetic effects explained a substantial proportion of variation in relative energetic allocation to self. Models fitted without a phylogenetic random effect (not shown) exhibited a strong negative effect of breeding latitude on POL, in keeping with previous reports (Muller & Nisbet 2000; Yanco et al 2022). That phylogenetic effects are apparently confounded with biogeography offers an intriguing avenue for future research taking a macroevolutionary approach to these questions but extends beyond the scope of the present analysis.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, we found that phylogenetic effects explained a substantial proportion of variation in relative energetic allocation to self. Models fitted without a phylogenetic random effect (not shown) exhibited a strong negative effect of breeding latitude on POL, in keeping with previous reports (Muller & Nisbet 2000; Yanco et al 2022). That phylogenetic effects are apparently confounded with biogeography offers an intriguing avenue for future research taking a macroevolutionary approach to these questions but extends beyond the scope of the present analysis.…”
Section: Discussionsupporting
confidence: 90%
“…Because we expect POL to be constrained to [0, 1], we modeled it as beta distributed. We also included niche dissimilarity as a predictor on the precision parameter for the beta distribution (φ) based on previous reports (Yanco et al 2022). To control for phylogenetic relatedness among the species in our sample we implemented a phylogenetic generalized mixed model approach (Lynch 1991; Garamszegi 2014).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, while polar oceans may increase in temperature, they will remain strongly seasonal. This result is one of the novel predictions of our model that warrants further investigation; while there is increasing attention to latitudinal trends in physiological processes in terrestrial systems (Yanco et al 2022), the role of seasonality in driving life history evolution is still poorly understood.…”
Section: Discussionmentioning
confidence: 76%